2014
DOI: 10.1080/08870446.2014.982652
|View full text |Cite|
|
Sign up to set email alerts
|

Mindfulness, physical impairment and psychological well-being in people with amyotrophic lateral sclerosis

Abstract: The available data indicate that a psychological construct - mindfulness - can attenuate the progress of a disease that is believed to be almost solely biologically driven. The potential implications of these results extend well beyond ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 48 publications
1
35
1
5
Order By: Relevance
“…It has been noted that psychological approaches to symptom management in ALS are under-explored and under-utilized. Mindfulness has been shown to impact QoL and psychological well-being but other psychologically-based studies are rare (28,29). The results of our study point to the importance of acknowledging the role of selfefficacy in the pain experience.…”
Section: Discussionmentioning
confidence: 50%
“…It has been noted that psychological approaches to symptom management in ALS are under-explored and under-utilized. Mindfulness has been shown to impact QoL and psychological well-being but other psychologically-based studies are rare (28,29). The results of our study point to the importance of acknowledging the role of selfefficacy in the pain experience.…”
Section: Discussionmentioning
confidence: 50%
“…Finally, given that PF includes processes implicit in other therapeutic modalities, such as mindfulness-based approaches (Pagnini, Phillips, Bosma, Reece, & Langer, 2015), the results infer that investigation of mindfulness processes may also be warranted.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 91%
“…Several studies suggest, conversely, that ALS patients' QoL is independent of physical impairment (Simmons et al, 2000; Palmieri et al, 2010b; Pagnini, 2013), a phenomenon known as “disability paradox” (Carr and Higginson, 2001), although this relationship is still unclear and motor disability or ALS physical consequences are likely to play a crucial role in determining QoL (Ganzini et al, 1999; Lo Coco et al, 2005). QoL has also been negatively associated to psychological variables such as suffering, sense of burden and hopelessness and positively related mainly to spirituality (McLeod and Clarke, 2007; Pagnini et al, 2011), caregiver relations (Chiò et al, 2004), and mindful attitude (i.e., not evaluating a situation or a context only through previous categorizations, but actively making new distinctions by assuming multiple viewpoints and perspectives; Pagnini et al, 2014a). Fegg et al (2005) and Roach et al (2009), highlight a usually undervalued viewpoint, i.e., personality and personal attitudes strongly modulate and shape in a unique manner the possible reactions to ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Johnston et al (1999) and Krampe et al (2008) found that mood and personality traits can strongly influence the survival rate of ALS patients. Recently, Pagnini et al (2014a) showed on a large sample of people with ALS that a mindful attitude attenuates the ALS progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation